Strategi Perkuliahan dan Praktikum Zoologi Vertebrata dengan Menggunakan Multimedia untuk Meningkatkan Kompetensi Dasar Calon Guru IPA Biologi di UMMY Solok - Roza, Helvita (Jurusan PIPS FKIP UMMY Solok, 2019)
Vertebrate Zoology is a course that provides scientific insight into high-level animals with the characteristic of having vertebral bones to support their bodies. So many scientific terms and characteristics of each animal group in this course, cause problems for students to learn. Efforts to compensate for the demands of aspects of learning in vertebrate zoology learning, it is not enough to use only one type of teaching media. This study aims to examine the use of multimedia used in lectures and vertebrate zoology practicums to improve the basic competencies of prospective science teacher students. The activity model refers to the class action research model. Evaluation of learning outcomes is done by looking at the ability of students to understand each material delivered through: unit tests pretest midterms, final semester exams and structured assignment scores. The evaluation results showed that the readiness of students to receive lecture material was seen from unit I tests of 54.50% and II at 67.51%. Student readiness faces practicum material at 49.30%. The structured task results obtained 37.80% doing practicum well. Practical UTS results (average 53.18) and practicum UAS (average 67.33) showed an increase in learning outcomes by 78.98%. The UTS theory results (mean 51.42) and UAS theory (average 58.96) indicate an increase in learning outcomes by 87.21%. Thus, it can be concluded that the use of multimedia can improve the competency of prospective science teacher students, seen from the knowledge, skills, and basic values ??reflected in their thinking habits.